Possibilities for misuses of virtual currencies in money laundering process and financing terrorism - Stajić, Ljubomir; Mirković, Vladan M; Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Virtual currencies represent data sets that arise by solving the most complex mathematical equations by using the most sophisticated computer technologies and which are recognized as some kind of value that stands in a certain relationship with national currencies. Protection of virtual currencies from falsification or any other interference with their functioning is guaranteed by cryptographic algorithms, therefore virtual currencies can be considered as a unique financial instrument in a technological sense. The dangers of misusing virtual currency come from a non-adapted environment in which they operate and which can turn them into an effective tool for money laundering, financing of terrorism and other more serious forms of crime.